Fibrous porous silica microspheres decorated with Mn3O4 for effective removal of methyl orange from aqueous solution. Issue 128 (14th December 2015) - Tian, Yaxi; Liu, Yan; Sun, Zebin; Li, Haizhen; Cui, Guijia; Yan, Shiqiang
Abstract : In this work, trimanganese tetraoxide (Mn3 O4 ) functionalized fibrous porous silica microspheres (KCC-1) with well-dispersed and excellent adsorption capacities were successfully synthesized by a simple and mild method for the first time. Abstract : In this work, trimanganese tetraoxide (Mn3 O4 ) functionalized fibrous porous silica microspheres (KCC-1) with well-dispersed and excellent adsorption capacities were successfully synthesized by a simple and mild method for the first time. Various conditions such as initial dye concentration, contact time, solution pH and temperature were investigated. Experimental results indicated that the content of Mn coated on KCC-1 was estimated to be around 14% (wt%) showing excellent adsorption capacity. The maximum adsorption capacity was determined to be q max = 746 mg g −1 and the adsorption equilibrium could be reached within 120 min. The results showed that both Langmuir and Freundlich models fitted the experimental data very well. The overall rate process was influenced by intra-particle diffusion and external mass transfer. Moreover, the thermodynamic parameters indicated that the adsorption was spontaneous and exothermic.